Metodología para un sistema de información gerencial como apoyo a la toma de decisiones del área de farmacia del hospital General Enrique Garcés. - Vizuete Olmos, Wladimir Francisco (2020)
General Enrique Garcés Hospital, with its labor day by day, has a great variety of data that are generated for several departments like the administration or the operational such as the Institutional Pharmacy. Currently, the Hospital Pharmacy does not get a data system that allows the management of its information to have the knowledge in order to be a big input for making decisions in a Manager Level. How to benefit General Enrique Garcés Hospital Management with a Business Intelligence Managerial Information System that processes and analyzes the storing data from its departments to generate knowledge contributing to decisions making? Stablishing an Intelligence Method in a Manager Level of the Institutional Pharmacy in Enrique Garcés Hospital for the management, processing and analysis of its data that allows giving reports of medicines in a truthful and timely way to support decisions making in a Manager Level. For the knowledge production of information of the Pharmacy, it will use as SEMMA data Mining Methodology Process, and for the analysis of the information of medicines, the computer tool MICROSOFT POWER BI which, nowadays, is considered as the most successful one. In this way, it includes a Business Intelligence Methodology that will be adapted for every single likely change that appears in the service of the Pharmacy without any problem because it is very flexible and it could obtain a variety of knowledge.